Preparing new teachers : operating successful field experience programs (Thousand Oaks, Calif. : Corwin Press, 1995)
Preparing New Teachers, the second book of four books, presents practical ideas for the day-to-day operation of field experience programs. It provides guidelines and prototype programs that allow university teacher educators, as well as those who supervise field experiences in K-12 schools, to understand what is required to run a smooth field experiences program. Slick includes information on state department requirements for certification and the legal and other aspects of placement and displacement procedures. The multifaceted responsibilities of the field experiences director are also spotlighted. Preparing New Teachers is a timely and valuable resource for organizing "state-of-the-art" field experience programs. Through vignettes and descriptive advice, it guides university education faculty and staff in the ongoing organization, revision, and implementation of successful field experience programs.
Includes bibliographical references and index.
Keywords: Student teaching -- Planning. -- United States; Student teachers -- Supervision of -- United States